ROP and crystallization behaviour of partially renewable triblock aromatic-aliphatic copolymers derived from L-lactide. (5th January 2020) - Flores, Irma; Martínez de Ilarduya, Antxon; Sardon, Haritz; Müller, Alejandro J.; Muñoz-Guerra, Sebastian
Graphical abstract: Highlights: Novel triblock aromatic aliphatic copolyesters were successfully prepared by ROP. TBD organocatalyst does not promote transesterification due to the low temperatures used. The inner aromatic-aliphatic segments of the ABA copolymers are able to crystallize in a broad composition range. Thermal and structural properties are independent on PLA content up to a high concentration. Abstract: Two series of partially biobased ABA triblock copolyesters were successfully prepared by ring-opening polymerization (ROP) of L -lactide initiated by two telechelic polyester polyols using an organic catalyst. B blocks were made of telechelic poly(hexamethylene terephthalate) (PHT) and poly(hexamethylene 2, 5-furandicarboxylate) (PHF), respectively, with average molar masses of around 3500 g mol −1 and A blocks were made of poly(lactic acid)s (PLA) of different block lengths. For each series, four copolymers with different PHT/PLA and PHF/PLA compositions were prepared by varying the feed molar ratios. The triblock structure of the obtained copolymers was ascertained by 13 C NMR, which confirms that the organic catalyst employed does not promote transesterification reactions at the low temperatures used for the reaction. All copolyesters were thermally stable under inert atmosphere up to around 300 °C. For all synthesized copolyesters, the PLA blocks were unable to crystallize, mainly due to racemization reactions taking place during L -lactide ROP. Both, PHT and PHF blocks were able to crystallize and their thermal and structural properties ( T m, T c, X c and lamellar thickness) were independent on PLA content until its concentration was very high and topological restrictions difficulted crystallization. According to SAXS, most copolymers were found to be miscible in the melt. Both PLA- b -PHT- b -PLA or PLA- b -PHF- b -PLA triblock copolymers showed a single T g indicating that the components are miscible in the amorphous state.